PENGARUH INVESTASI, PENGELUARAN KONSUMSI RUMAH TANGGA DAN PENGELUARAN PEMERINTAH TERHADAP KESEMPATAN KERJA SERTA KESEJAHTERAAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI BALI - Antari, Diah Windu; Marhaeni, A. A. I. N (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 11 (2020): VOL 9 NO 11, NOVEMBER 2020 (2390 - 2617), 2020)
The purpose of this study was to analyze the effect of investment, household consumption expenditure and government expenditure on employment opportunities and community welfare in the regencies / cities of Bali Province. The data used are secondary data, with 72 observations. The analysis technique used is path analysis. The results showed that, household consumption expenditure and government expenditure had a positive effect on employment opportunities, investment and household consumption expenditure had a positive effect on people's welfare. Government expenditure and employment opportunities do not have a positive effect on people's welfare. Job opportunities do not mediate the effect of investment, household consumption expenditure, and government expenditure on community welfare. Keywords: Investment, Household Consumption Expenditures, Government Expenditures, Community Welfare